2008
DOI: 10.1165/rcmb.2006-0295oc
|View full text |Cite
|
Sign up to set email alerts
|

8-iso-PGE2 Stimulates Anion Efflux from Airway Epithelial Cells via the EP4 Prostanoid Receptor

Abstract: Isoprostanes are biologically active molecules, produced when reactive oxygen species mediate the peroxidation of membrane polyunsaturated fatty acids. Previous work has demonstrated that the isoprostane 8-iso-prostaglandin E(2) (PGE(2)) stimulates cystic fibrosis transmembrane conductance regulator (CFTR)-mediated transepithelial anion secretion across the human airway epithelial cell line, Calu-3. Since isoprostanes predominantly achieve their effects via binding to prostanoid receptors, we hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…Palmer and colleagues showed in Calu-3 cells that PGE 2 activated CFTR via EP2-Rs and EP4-Rs (12). Joy and Cowley, in contrast, reported that Calu-3 cells express all four known EP-R subtypes, but point to EP4-Rs in the regulation of CFTR-dependent iodide efflux (28). Via RT-PCR, we only detected EP4-Rs in our Calu-3 cells, and EP4 inhibition was sufficient to prevent CFTR activation, confirming the results of Clayton and colleagues (29).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Palmer and colleagues showed in Calu-3 cells that PGE 2 activated CFTR via EP2-Rs and EP4-Rs (12). Joy and Cowley, in contrast, reported that Calu-3 cells express all four known EP-R subtypes, but point to EP4-Rs in the regulation of CFTR-dependent iodide efflux (28). Via RT-PCR, we only detected EP4-Rs in our Calu-3 cells, and EP4 inhibition was sufficient to prevent CFTR activation, confirming the results of Clayton and colleagues (29).…”
Section: Discussionsupporting
confidence: 88%
“…The production of PGE 2 via PLA 2 and COX activation and its paracrine stimulation of EP-Rs were proposed as a mechanism to amplify not only the engagement of A2B-Rs, but also of PARs (7,8,11,12,27,28). Controversy continues regarding which PGE 2 receptor subtype is involved in this signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that isoprostanoids, formed by nonenzymatic peroxidation, activated the Cl 2 secretion response in bovine tracheal epithelial cultures and Calu-3 cells (19,20). In contrast, we found that H 2 O 2 stimulated COX activity, resulting in prostanoid formation, as previously described in other cells (27).…”
Section: Role Of Cox In Hydrogen Peroxide Stimulation Of I Scsupporting
confidence: 86%
“…However, hydroxyl radicals did not appear to play a role in the effects of H 2 O 2 on NHBE cells. Furthermore, isoprostanes have been reported to stimulate CFTR activity in cell lines (19), but the inhibition of H 2 O 2 -induced CFTR currents by COX inhibitors in NHBE cells suggests that isoprostanes, which are directly generated by H 2 O 2 exposure, were not responsible for the observed effects in fully differentiated airway epithelial cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation